Cellulose Acetate/Activated Carbon Composite Membrane with Effective Dye Adsorption Performance. Issue 12 (2nd December 2019) - Zhao, Xiaoyan; Huang, Chen; Zhang, Shuai; Wang, Chenyi
Abstract: Cellulose acetate (CA) and activated carbon (AC) were used as base material and additive, respectively, to prepare CA/AC composite membranes. By adjusting the AC content (5%, 10%, 15%, and 20%), the morphology and the adsorption capability of the samples for target dyes were studied. The results showed that the surface flatness and compactness of the barrier layer deteriorated with increasing AC content. In addition, the pore size and structures of the supporting layer became large due to the partial agglomeration of the AC in the CA. The relationship between adsorption time and adsorption capability was investigated. It was found that the 15% AC composite membrane possessed the highest adsorption efficiency for acid blue dye. The adsorption equilibrium was 58.69 mg/g for 60 mg/L acid blue dye at 120 min. For acid yellow and acid dark dye, the adsorption equilibria were 58.23 and 58.34 mg/g, respectively.